The Role of Indigenous Peoples in Managing the Potential of Nature Tourism in Samber and Binyeri Villages - Ayu Kurnia Utami; Muh. Ridwan Yunus; Ismiyati Ismiyati (Department of Public Administration, Muhammadiyah University of Makassar, 2021)
Beach being the mainstay of the tourism sector in the Samber-Binyeri's Village where the community dominated as customary society that still applies the customary rules in the life of a society as local wisdom identity. By combining the description of management and the concept of people-centered community participation, this research aims to know the role of customary society in managing the potential of nature tourism in the village of Samber-Binyeri. Used descriptive qualitative exploratory approach with observational, interviews, and documentation research techniques then done by triangulating the data, obtained a result as the role of the civil society based on the level of participation perceived the delegated power. The nature of community involvement that is people centered by observing public values, economic values, cultural and social values, political values, educational values and ecological values.